2022
DOI: 10.1111/jdi.13777
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cell function and body mass index are predictors of exercise response in elderly patients with prediabetes

Abstract: Aims/Introduction To explore the predicting factors of exercise response (whether the participants converted to diabetes) in elderly patients with prediabetes. Materials and Methods This is a retrospective subgroup analysis of the registered clinical trial with previous publication of the same cohort. A total of 248 participants with prediabetes were randomized to the aerobic training ( n = 83) group, resistance training ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Among these, 3117 were excluded based on their titles and abstracts, leaving 105 papers for full-text examination. Finally, 10 RCTs were included in the review and meta-analysis ( 14 , 15 , 19 26 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 3117 were excluded based on their titles and abstracts, leaving 105 papers for full-text examination. Finally, 10 RCTs were included in the review and meta-analysis ( 14 , 15 , 19 26 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All aerobic training was performed under supervised conditions. Modes of training include aerobic dance ( 14 , 19 21 , 24 , 25 ), treadmill running ( 15 , 26 ), walking ( 15 , 22 ), and mixed aerobic exercise ( 23 ). In nine studies, exercise intensity was reported as maximum heart rate (HRmax), maximum heart rate reserve (HRRmax), or heart rate reserve (HRR) with a median intensity and range of 65% (50%-75%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted on elderly pre‐diabetic patients found that the type of exercise did not significantly affect the glucose response to exercise 23 . However, it was observed that initial poor HbA1c levels and a high body mass index were associated with a poor response to exercise in terms of blood glucose tolerance and HbA1c reduction.…”
Section: Study Subjects Intervention Component Duration Hba1c Fpgmentioning
confidence: 99%